PERANCANGAN DAN ANALISIS PROSES BISNIS APLIKASI ADOPSI HEWAN PELIHARAAN - Geasela, Yemima Monica; Ariawan, Eko; Lee, Francka Sakti; Andry, Johanes Fernandes; Verawaty, Verawaty; Kezia, Kezia (ISTEK WIDURI, 2025)
The pet adoption application aims to simplify and speed up the animal adoption process by connecting potential adopters with adoption service providers. This research aims to design and analyze business processes in this application using the Business Process Model and Notation (BPMN) approach. BPMN is used to visualize workflows in a structured manner and identify potential inefficiencies and Opportunities for improvement in existing systems. The research process involved collecting data through interviews, observations, and analysis of documentation from animal adoption organizations and potential adopters. BPMN modeling is carried out to describe business processes in two conditions: before and after application implementation. Analysis is carried out to evaluate changes in efficiency, effectiveness and user experience after the system is implemented. The research results show that this application is able to simplify the adoption process by reducing the number of manual steps, speeding up adoption application processing, and increasing user engagement. In addition, recommendations for improvements are provided to further improve integration between processes and minimize the potential for operational errors. This research concludes that the BPMN approach is effective in designing and analyzing pet adoption application business processes. These findings contribute to the development of similar applications by providing guidance for creating workflows that are efficient, standardized, and responsive to user needs.